Key stakeholder perspectives on the barriers and solutions to pharmacy practice towards complementary medicines: an Australian experience - Carolina Oi Lam Ung; Joanna Harnett; Hao Hu (BMC, 2017)
Abstract Background Although pharmacists are entrusted to play a role in ensuring the safe and appropriate use of all medicines, in general, the inclusion of complementary medicines (CMs) into their professional practice has not been observed. The purpose of this study was to explore the perceptions and opinions of pharmacists and 8 key stakeholder leaders regarding the barriers that hinder pharmacists from providing care related to the use of CMs by patients/consumers and to identify solutions that would support pharmacists' in extending their role in this area. Methods Semi-structured key informant interviews were conducted with 2 practicing pharmacists, 1 pharmacy owner, 1 key representative of a pharmacist professional organization, 1 key representative of a consumer advocacy group, 1 key representative of a medical professional organization, 1 key representative from a complementary medicine practitioner professional organization, 1 leader within a pharmacy school, 2 senior staff from a regulatory authority, and 1 key representative of the complementary medicine industry in Australia. Results A total of 9 barriers were identified in this study. Barriers including a lack of CMs knowledge, doubts about the evidence-base, a lack of research skills and access to reliable and reputable information dominated the discussions. A total of 7 solutions were proposed. Of those, the integration of CMs curricula into under-graduate and professional pharmacy education, and defining a clearer role for pharmacists' standard of practice were considered the most important. Apposing opinions about the role of naturopaths in pharmacies were identified.. Conclusion It is anticipated that pharmacists will be required to formalise a role in ensuring the safe and appropriate use of complementary medicines to fulfil their professional and ethical responsibilities. However, pharmacists in general are not ready to take up this extended role. Individual key stakeholder groups have considered the existing barriers and have proposed solutions that are isolated measures. To facilitate further developments related to CMs and the professional practice of pharmacy, collaborative efforts between key stakeholders are needed to strategically plan and execute an extended role in a unified manner.